2015
DOI: 10.1016/j.jccase.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Pathological evaluation of massive left atrial calcification 35 years after mitral-aortic valve replacement

Abstract: IntroductionAlthough calcification of the left atrium is relatively common in the setting of long-lasting rheumatic valve disease, massive calcification of the left atrium, also known as ''porcelain atrium [1],'' ''coconut atrium [2], '' or ''mold-like calcification [3],'' is a rare condition. The left atrial calcification is described as a high-density ring encircling the left atrium on chest X-ray. Noncontrast computed tomographic (CT) scan of the thorax reveals deposition of calcification in the wall of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Longstanding rheumatic mitral valve disease or previous mitral valve surgery may lead to calcification of the left atrium as an uncommon complication. It has been suggested that the calcification of the left atrium is a response to the chronic strain forces present in the setting of mitral disease [13,14]. A review by Harthorne et al has remarked that the interatrial septum is often spared and free from calcification [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longstanding rheumatic mitral valve disease or previous mitral valve surgery may lead to calcification of the left atrium as an uncommon complication. It has been suggested that the calcification of the left atrium is a response to the chronic strain forces present in the setting of mitral disease [13,14]. A review by Harthorne et al has remarked that the interatrial septum is often spared and free from calcification [1].…”
Section: Discussionmentioning
confidence: 99%
“…Longstanding severe rheumatic mitral stenosis is associated with changes in the atrial chamber dimensions. It is not specifically known whether there are changes in the IAS dimensions proportionate to the increasing severity of rheumatic mitral stenosis, however, there is some evidence that there may be relative sparing of the interatrial septum [[12], [13], [14]]. Since no previous studies have reported echocardiographic changes in the IAS thickness or thinning in valvular heart disease patients; the aim of this study was to evaluate IAS thickness by transesophageal (TEE) in a consecutive series of patients undergoing percutaneous balloon mitral valvuloplasty for moderate to severe rheumatic mitral stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical access to the mitral valve in cases of complete calcification of the left atrium, including the interatrial septum becomes very difficult. Out of 16 reported cases in the published literature only 4 patients could be operated on [51][52][53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Surgical Approach and Managementmentioning
confidence: 99%
“…In fact, despite the significant decrease in the national prevalence of rheumatic fever (RF), left atrial calcification remains a relatively common finding on imaging, both on chest and cardiac computed tomography [2,3]. Importantly, the body of literature gives other possible causes of left atrial calcification, including mitral valve disease and mitral valve replacement, end-stage renal disease, history of radiation therapy, and non-specific endocarditis, but no study has demonstrated modern distribution of pathology [4][5][6][7][8][9][10][11][12]. Indeed, the modern proliferation of endomyocardial ablation techniques and catheter-directed therapies for structural heart disease, raises the question of iatrogenic damage [13,14].…”
Section: Introductionmentioning
confidence: 99%